JUSTIFICATION OF MEDICO-LEGAL AUTOPSY IN CONVENTIONAL CUSTODIAL DEATHS (Journal of Forensic Medicine & Toxicology, 2025)
Background: Custodial deaths may be defined as ‘death occurring while a person is in the custody of law enforcement officials or in a correctional facility.’ Medicolegal autopsy in custodial deaths, emphasized by NHRC, is crucial for justice and accountability. As per NHRC guidelines, videography is essential during postmortem of deaths in police custody however its requirement in cases of death in jail will be applicable only if the magistrate raises any suspicion of foul play in inquest or any complaint is made before concerned authorities. It is also evident from the guidelines that NHRC never states that death in Mental Health Care Establishments or in Homes will be considered as ‘Custodial deaths’ and postmortem examination under videography is not mandated in all such cases. However, due to some unknown reason we see all deaths in Mental Health Care Establishments and Homes where the patients were admitted under Court order, are considered as ‘Custodial deaths’ and sent for Medicolegal autopsy even when the MCCD mentions the cause of death as ‘natural’.
Keywords: essential during; establishments; Custodial